2008
DOI: 10.1007/s00262-008-0520-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BCG stimulus on proinflammatory cytokine production in laryngeal cancer

Abstract: BCG is able to modulate the immune response of patients with advanced supraglottic laryngeal cancer in vitro, increasing the secretion of TNF and IL-6 by macrophages during the postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Additionally, increased production of TNF-α by PBMC from MB patients was observed in the presence of LPS after the application of BCG-id ( P = 0.017), suggesting a nonspecific immune stimulatory action of BCG on the innate immunity response 30. This is a very interesting response in multibacillary leprosy, where TNF-α acts by inducing macrophage activation, thus favoring destruction of the parasite and the maintenance of IFN-γ production 31.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, increased production of TNF-α by PBMC from MB patients was observed in the presence of LPS after the application of BCG-id ( P = 0.017), suggesting a nonspecific immune stimulatory action of BCG on the innate immunity response 30. This is a very interesting response in multibacillary leprosy, where TNF-α acts by inducing macrophage activation, thus favoring destruction of the parasite and the maintenance of IFN-γ production 31.…”
Section: Discussionmentioning
confidence: 98%
“…In a previous study, we evaluated the production of TNF-α and IL-6 in the supernatant of adherent cells cultured from peripheral blood mononuclear cells (PBMCs) isolated from patients with supraglottic laryngeal cancer before and after surgical treatment. We found that BCG is able to modulate the immune response of these patients (6). In this study, we evaluated the production of IFN-γ and IL-10 by cultured PBMCs isolated from patients with advanced supraglottic laryngeal cancer.…”
Section: Introductionmentioning
confidence: 90%
“…Several articles have looked at the detailed effect of BCG on cancer cell lines and on human leukocytes in vitro, including two papers using leukocytes from head and neck cancer patients (60)(61)(62)(63). Overall, BCG increased production of most cytokines measured but most notably IL-6, tumor necrosis factor and interferon-gamma, but not IL-2.…”
Section: Bcg As Direct Anticancer Therapy (Alone or In Combination With Existing Treatments)mentioning
confidence: 99%